Everybody Jumping on the Savannah Grass: How Carnival Became a Symbol of Trinidad and Tobago's National Culture - Brittney Bahadoor (Caribbean Studies Students' Union, 2023)
This paper focuses on the history of Carnival in Trinidad and Tobago and how the country molded the event to become a staple of nationalism following independence in the 20th century. It explores the historical beginnings of Carnival, from slavery to indentured servitude to modern-day Trinidad. It looks at how becoming a mascot of Trinidadian culture was achieved in two ways-the representation and rhetoric of the event and how it became a commodity that politicians could use to prove a robust national culture to the world. It takes on central themes of unification, regardless of race, class, or culture, and how the event tells the history of this island, even with the costumes and enthralling music. It touches on how Carnival reflects cultural and political movements throughout the country's history, how it became significant for social changes after independence, and how it could withstand the infiltration of global capitalism and still present a story about Trinidad's culture and resilience. It is built around the argument that after independence in 1962, Trinidad needed a way to present itself as a nationalist country now that it does not have a metropole. This was achieved through the propping up of Carnival and allowing it to reflect various movements of the past. The goal is to add to the conversation that Carnival is not just a boisterous party on the island but also reflects the colonial history and diverse peoples and how it was able to modernize itself while sticking to these core values.